1971
DOI: 10.1007/bf02501221
|View full text |Cite
|
Sign up to set email alerts
|

Detonation characteristics of ammonite 6ZhV

Abstract: Modern drilling and blasting work comprises a wide range of processes, based on rock breaking by shock waves, stress waves, waves of rarefaction, and explosion products created by detonating explosive charges. The mechanical effect of an explosion on the ambient medium evidently depends both on the detonation characteristics of the explosives and on the properties of the medium (rock). Therefore, to find ways of increasing the efficiency of existing blasting methods, explosives, and shotfiring, importance atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1971
1971
1972
1972

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…However, the results of investigations in [3] revealed that the pressure and density of the explosion products do not increase markedly with increasing initial density of the explosives, whereas the polytropic exponent does show a marked increase. For comparison, Fig.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…However, the results of investigations in [3] revealed that the pressure and density of the explosion products do not increase markedly with increasing initial density of the explosives, whereas the polytropic exponent does show a marked increase. For comparison, Fig.…”
mentioning
confidence: 70%
“…To simplify calculation of the shock wave parameters at the interface, the shock adiabatic curve of the detonation products of ammonite 6ZhV charges with P0 = 1.0 g/cm s and d ~ 80 mm may be approximated by a single analytic equation: p = 43 u + 2u s + 0.8 u s, where u is in km/sec and p in 103 kg/cm 2. A previous communication [3] gives the pressures at the Chapman-louguet points of charges of different diameter, necessary for the calculations.…”
mentioning
confidence: 99%
“…The higher the energy capacity in the loading of the medium, the greater the value of c~. For example, for argillaceous silt, limestone,and marble, which have different energy capacitites, the ratio of the c~ values satisfies the inequality C~as > ali m > ama r (2) and their values are 0.1214, 0.0766, and 0.0442, respectively.…”
Section: E~ojmentioning
confidence: 95%
“…The experimental procedure and measurement methods for the wave parameters are discussed in [1][2][3].…”
mentioning
confidence: 99%